Axial Ratio-Tuned Circularly Polarized Square Patch Antenna with Long Stubs - Y. Sung (International Journal of Antennas and Propagation)
In this letter, we propose a circularly polarized (CP) square antenna that can change the frequency of the minimum axial ratio (AR). The proposed antenna is designed in a very straightforward manner by applying four long stubs to a square patch. The length of one of the stubs is different from that of the other three stubs, and the structural asymmetry is realized in such a manner that the CP characteristic is conveniently obtained. The proposed antenna can independently adjust the resonant frequency and the frequency of the minimum AR value. Therefore, the resonant frequency and the frequency at which the minimum AR value appears can be easily matched. By applying this method, six antennas with the adequate CP characteristic, notwithstanding the varied stub widths (1.5~6.5 mm), are designed.